Highly responsive photodetection based on bismuth ferrite ceramics: The roles of depolarization field and domain network. (February 2023) - Wang, Xin Hao; Chen, Shu-Yu; Chen, Cheng-Sao; Chen, Pin-Yi; Tu, Chi-Shun
Highlights: High photoconductive gain G∼25%, photoresponsivity R∼71 mA/W, specific detectivity D*∼2.4 × 10 11 Jones, and fast response time tr ∼6 × 10 −4 s were achieved in the ITO/Bi0.93 Gd0.07 FeO3 /Au heterostructure at the UV-A light (wavelength = 360 nm). The boosted photodetection is a collective effect of the p-n heterojunction, the depolarization field, the domain-wall nucleation and the polar nanodomain. The network of grain boundaries and domain walls provides electrically conductive pathways in the grain matrix. Abstract: This study presents the highly-sensitive, millisecond-response, and self-powered photosensors based on the indium-tin-oxide (ITO)/Bi0.93 R 0.07 FeO3 ceramic/Au heterostructures ( R = Nd, Gd) at 360-nm irradiation. Photocurrent density (Jph ), photoconductive gain (G), photoresponsivity (R) and specific detectivity (D*) were significantly boosted by an electric-field poling, and can reach 1.4 mA/cm 2, 25%, 71 mA/W and 2.4 × 10 11 Jones in the ITO/Bi0.93 Gd0.07 FeO3 /Au; 0.17 mA/cm 2, 14.5%, 42 mA/W and 2.6 × 10 12 Jones in the ITO/Bi0.93 Nd0.07 FeO3 /Au. Fast response times of 0.6 ms and 1.0 ms are respectively detected in the ITO/Bi0.93 Gd0.07 FeO3 /Au and ITO/Bi0.93 Nd0.07 FeO3 /Au. The enhanced photodetection is driven collectively by the p-n heterojunction, the depolarization field, and the electric-field-induced domain-wall nucleation. The complex network consisting of grain boundaries and nanoscale domain walls provides electrically conductive passages in the grain matrix. This work delivers an energy self-sufficient route using the polycrystalline rare-earth-doped BiFeO3 ceramics for the high-performance photodetection in the ultraviolet-A spectrum. Graphical Abstract: Image, graphical abstract